Simulation of incoherent radiation absorption in 3C-, 6H- and 4H-SiC at rapid thermal processing - Agueev, O.A.; Svetlichny, A.M.; Soloviev, S.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
For 3C-, 6H- and 4H-SiC polytypes of different conduction types and with various impurity concentrations we investigated absorption of incoherent radiation from the near IR spectral region at rapid thermal annealing. General regularities of both radiation absorption and sample heating are considered. We evaluated various processing modes; one should take this into account when developing technological procedures based on rapid thermal processing for SiC.